Forage seed production in Thailand and the Greater Mekong Subregion (GMS): Exploration of development opportunities - Tiemann, Tassilo T. (International Center for Tropical Agriculture, 2023)
This study was commissioned by the Alliance of Bioversity International and CIAT to assess the viability of enhancing forage selection and dissemination and targeting breeding and selection efforts focusing on the specific needs of South-East Asian farming systems. The opportunity to be assessed is to strengthen the Alliance’s collaboration with the Thai government in the framework of improved Tropical Forages. The study aims to address bottlenecks for forage seed supply systems for: a) the internal Thai market; b) for export in the SEA region, specifically to Vietnam, Laos and Cambodia. This study thus aims at providing a good understanding of the forage seed systems in Thailand, its links with the wider SEA region, and reviews high-level stakeholder engagements with government authorities and the private sector. It provides an overview of forage seed certification options available in-country to ensure seed quality (e.g., purity and germination), requirements for varietal registration, and regulations for import/export of seeds.